I Improving Student Learning Achievement in Natural Sciences Subject in Class VII B at SMP Negeri 5 Kendari (Junior High School) Through The Type of Team Games Tournaments (TGT) Cooperative Learning Model (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
This study aims to use the TGT cooperative learning model to improve the learning achievement of class VII-B students of SMP Negeri 5 Kendari in Natural Science learning. This research was conducted in class VII-B SMP Negeri 5 Kendari. The subjects studied were students of class VII-B, totaling 34 students, consisting of 22 girls and 12 boys. The results of the study in three learning cycles were: 1) The learning outcomes achieved by students in cycle I who obtained a value of ≥ 70 were 17 students (50%), 2) the learning outcomes achieved by students in cycle II who obtained a value of ≥ 70 as many as 22 students (64.7%), and 3) the learning outcomes achieved by students in cycle III who obtained a value of ≥ 70 were 29 students (85.3%). There has been an increase in learning outcomes in cycle I when compared to the initial test where 17 students completed learning when compared to 14 students in the initial test. In cycle III there has been an increase in learning outcomes when compared to the second cycle where the number of students who completed classically was 29 students (85.3%) with an average value of 75.0 when compared to 22 students who completed the second cycle (64, 7%) with an average value of 69.6. The use of the Team Games Tournament (TGT) type cooperative learning model in Natural Science learning can improve the learning achievement of class VII-B students of SMP Negeri 5 Kendari.